2021
DOI: 10.29121/granthaalayah.v9.i5.2021.3938
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Characteristics as a Reliable Tool for Assessing the Quality of Accounting Information: An Overview Study

Abstract: The accounting information contained in the financial reports is considered to be of a quality if it possesses a set of characteristics. Professional organizations have been concerned with the issuance of standards and the determination of characteristics related to the quality of accounting information. This paper aims to clarify the dependability on the qualitative characteristics of accounting information as an indicator of the quality of accounting information. The historical approach is used for the purpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Syrtseva and Cheban believed that accounting compliance system was a theory to ensure the development and operation of enterprise accounting information quality, then the methodological basis of the research was general science and special cognitive methods [4]. Alasbahi and Ishwara believed that if the accounting information contained in the financial report has a set of characteristics, then the financial report would be considered to be of quality [5]. However, it is more important to pay attention to the transformation of accounting informatization, which is not considered in the above research.…”
Section: Related Workmentioning
confidence: 99%
“…Syrtseva and Cheban believed that accounting compliance system was a theory to ensure the development and operation of enterprise accounting information quality, then the methodological basis of the research was general science and special cognitive methods [4]. Alasbahi and Ishwara believed that if the accounting information contained in the financial report has a set of characteristics, then the financial report would be considered to be of quality [5]. However, it is more important to pay attention to the transformation of accounting informatization, which is not considered in the above research.…”
Section: Related Workmentioning
confidence: 99%
“…According to the findings, the key goal of the corporate governance is to reestablish confidence in and control over accounting information by accountability and control. Improving the information quality by the establishment and enforcement of accounting and auditing standards Alasbahi (2020) showed that implementing corporate governance gives rise to greater accountability and administrative control, supports the application of international standards, enhances disclosure, and transparency, and strengthens the audit committee's tasks, internal audits, and external audits. All positively affects the accounting information quality.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They improve users' ability to examine and analyze financial statements by making information more comparable (Madawaki, 2012). According to Alasbahi and Ishwara (2021), the essential purposes of the International Accounting Standards Board (IASB) stand is to increase and enhance the levels of confidence in financial reporting, for instance, the adoption of IFRS. It is important due to the International Financial Reporting Formula, as it makes businesses and organizations of various activities to be more aware and closer to the international financial market.…”
Section: Introductionmentioning
confidence: 99%